Survey on Big data analytics in Healthcare Domain - Praveena, M; Kameswara Rao, M (International Journal of Engineering and Technology, 2018)
These days, amount of data in different formats is increasing rapidly due to the use of different technologies and increasing use of Internet. In previous decades, data even if it is large, its format and sources are limited but now-a-days, massive amount of data is collected from different sources in different formats. This concept gave rise to new concept called â€œBig Dataâ€ which is a present trend to deal with the data. Analytics is one more crucial topic under big data which deals with the analysis and its integration with business process. Many books, tools, sub topics were raised from the â€œBig Dataâ€ where it takes a large amount of time to understand and to start to work with it. Hence, we are going to give a review on â€œBig Dataâ€, â€œBig Data Analyticsâ€ and its tools briefly. Here, Healthcare is taken as example to get the brief understanding on â€œBig Data and Analyticsâ€. This paper, we have also reviewed various big data frameworks with respective to data sources, application area, analytical capability and made study on various papers by presenting their methodology, tools, advantages and limitations.Â Â